Integrasi Nilai-Nilai Hindu dalam Bahasa dan Sastra Bali: Sebuah Pendekatan Kultural dan Spiritualitas - Luwih, I Made (Kamaya: Jurnal Ilmu Agama, 2025)
Balinese language and literature are important elements in preserving Balinese culture as well as a medium for conveying Hindu teachings. As an integral part of Balinese people's lives, Balinese language and literature not only function as a means of communication, but also as a vehicle for inheriting moral, spiritual, and local wisdom values ​​rooted in Hindu teachings. This study aims to explore the relevance of Hindu teachings in the formation of Balinese language and literature values, as well as their role in strengthening the cultural identity of Balinese people in the era of globalization. Using a qualitative approach with a descriptive-analytical method, this study analyzes Balinese literary texts such as kakawin, kidung, and lontar, and observes the use of Balinese language in traditional ceremonies and daily practices. Data were collected through literature studies, participatory observations, in-depth interviews with traditional figures and literary experts, and field documentation. The results of the study show that Hindu teachings, such as the concepts of Tri Hita Karana and Tat Twam Asi, are deeply integrated into the structure of Balinese language and literary works. Balinese literature plays an important role in the moral and spiritual education of the community, especially through its use in religious rituals and formal learning. This study also identifies the challenges of preserving Balinese language and literature amidst the influence of foreign cultures and modernization. By understanding the role of Balinese language and literature as a medium for preserving Hindu values, it is hoped that these preservation efforts can be optimized, both through education and cultural policies. This research provides a significant contribution to strengthening Balinese cultural identity and preserving Hindu cultural heritage.